Learning Islam in “the land of Napoleon”: the dynamics of the politics of Islamic education in France - Iqbal, Mustamar Iqbal Siregar (the Faculty of Education and Teacher Training of the Institut Agama Islam Negeri (IAIN) Langsa, 2022)
This article discusses the development of Islamic education in France. The reviews in this paper are increasingly exotic because they stretch the historicity of Islamic education with a political-sociological perspective in the country that was once Napoleon Bonaparte’s zone of power. Although it uses literary research methods, analysis with a political-sociological approach supported by adequate literature data produces objective conclusions. Some of the findings of this methodological creation include: first, France is one of the European countries with a high Muslim population growth rate; second, the development of Islamic education in France reaped heavy resistance when secular ideology colored the country, but in the era of republican rule its development accelerated until the establishment of private Islamic educational institutions recognized by the government; and third, the sacred public space of Muslims is increasingly widespread both in terms of worship, the use of symbols (headscarves), and others.